A coiled coil switch mediates cold sensing by the thermosensory protein DesK. Issue 2 (3rd August 2015) - Saita, Emilio; Abriata, Luciano A.; Tsai, Yi Ting; Trajtenberg, Felipe; Lemmin, Thomas; Buschiazzo, Alejandro; Dal Peraro, Matteo; de Mendoza, Diego; Albanesi, Daniela
Summary The thermosensor histidine kinase DesK from Bacillus subtilis senses changes in membrane fluidity initiating an adaptive response. Structural changes in DesK have been implicated in transmembrane signaling, but direct evidence is still lacking. On the basis of structure‐guided mutagenesis, we now propose a mechanism of DesK‐mediated signal sensing and transduction. The data indicate that stabilization/destabilization of a 2‐helix coiled coil, which connects the transmembrane sensory domain of DesK to its cytosolic catalytic region, is crucial to control its signaling state. Computational modeling and simulations reveal couplings between protein, water and membrane mechanics. We propose that membrane thickening is the main driving force for signal sensing and that it acts by inducing helix stretching and rotation prompting an asymmetric kinase‐competent state. Overall, the known structural changes of the sensor kinase, as well as further dynamic rearrangements that we now predict, consistently link structure determinants to activity modulation.